Short-Form Videos Da’wah: Innovative Strategies To Foster Religious Moderation Among Generation Z - Istya Marwantika, Asna; Akbarani, Rizqi; Oluwaseun Dauda, Kazeem (International Journal Labs, 2026)
This study aims to explore innovative strategies for promoting religious moderation among Generation Z through short-form video da’wah content on digital platforms such as TikTok, Instagram Reels, and YouTube Shorts. Employing a qualitative descriptive approach supported by research and development (R&D) methodology, the study used digital media mining tools, including Google Trends, Brand24, and Analisa.io, to identify patterns, engagement levels, and influential contributors in the online discourse on religious moderation between 2019 and 2024. The data analysis revealed a significant increase in public interest and content creation among Gen Z users. Based on these findings, the study developed a Religious Moderation Guidebook that integrates Islamic communication ethics with digital media strategies. The guidebook was piloted among Islamic Communication and Broadcasting students who produced short-form videos reflecting national commitment, tolerance, anti-radicalism, and cultural accommodation principles. The results demonstrate that when guided by ethical frameworks and strategic communication planning, short-form video da'wah can effectively enhance youth engagement with messages of religious moderation. This research contributes theoretically and practically to Islamic communication scholarship and offers a replicable model for future digital da'wah efforts.